Neutralising antibodies block the function of Rh5/Ripr/CyRPA complex during invasion of Plasmodium falciparum into human erythrocytes. (24th April 2019) - Healer, Julie; Wong, Wilson; Thompson, Jennifer K.; He, Wengqiang; Birkinshaw, Richard W.; Miura, Kazutoyo; Long, Carol A.; Soroka, Vladislav; Søgaard, Teit Max Moscote; Jørgensen, Thomas; de Jongh, Willem A.; Weir, Christopher; et al.
Abstract: An effective vaccine is a priority for malaria control and elimination. The leading candidate in the Plasmodium falciparum blood stage is PfRh5. PfRh5 assembles into trimeric complex with PfRipr and PfCyRPA in the parasite, and this complex is essential for erythrocyte invasion. In this study, we show that antibodies specific for PfRh5 and PfCyRPA prevent trimeric complex formation. We identify the EGF‐7 domain on PfRipr as a neutralising epitope and demonstrate that antibodies against this region act downstream of complex formation to prevent merozoite invasion. Antibodies against the C‐terminal region of PfRipr were more inhibitory than those against either PfRh5 or PfCyRPA alone, and a combination of antibodies against PfCyRPA and PfRipr acted synergistically to reduce invasion. This study supports prioritisation of PfRipr for development as part of a next‐generation antimalarial vaccine.